Mutant UBQLN2 promotes toxicity by modulating intrinsic self-assembly - Sharkey, Lisa M. (Proc Natl Acad Sci U S A, 2018)
UBQLN2 is one of a family of proteins implicated in ubiquitin-dependent protein quality control and integrally tied to human neurodegenerative disease. Whereas wild-type UBQLN2 accumulates in intraneuronal deposits in several common age-related neurodegenerative diseases, mutations in the gene encoding this protein result in X-linked amyotrophic lateral sclerosis/frontotemporal dementia associated with TDP43 accumulation. Using in vitro protein analysis, longitudinal fluorescence imaging and cellular, neuronal, and transgenic mouse models, we establish that UBQLN2 is intrinsically prone to self-assemble into higher-order complexes, including liquid-like droplets and amyloid aggregates. UBQLN2 self-assembly and solubility are reciprocally modulated by the protein’s ubiquitin-like and ubiquitin-associated domains. Moreover, a pathogenic UBQLN2 missense mutation impairs droplet dynamics and favors amyloid-like aggregation associated with neurotoxicity. These data emphasize the critical link between UBQLN2’s role in ubiquitin-dependent pathways and its propensity to self-assemble and aggregate in neurodegenerative diseases.